Could woodworking have driven lithic tool selection?. Issue 156 (July 2021) - Gürbüz, Rebecca Biermann; Lycett, Stephen J.
Abstract: Understanding early stone tools, particularly relationships between form and function, is fundamental to understanding the behavioral evolution of early hominins. The oldest-claimed flake tools date to ca. 3.3 million years ago, and their development may represent a key step in hominin evolution. Flake form, and its relationship to function, has long been a focus of Paleolithic studies, almost exclusively with respect to meat acquisition. However, evidence for woodworking is now known from sites dating to 1.5 Ma. Additionally, Pan troglodytes are known to manufacture wooden tools for hunting and foraging, thus creating a phylogenetic (parsimony) argument for more ancient woodworking. However, few studies examining woodworking and Paleolithic tools have been completed to date. Indeed, it remains an open question whether woodworking may have instigated specific selective demands on the form of early stone tools. Here, we conducted an experiment testing the comparative woodworking efficiency (measured by time) of small and large flakes. Two groups of participants used either a relatively small or large unretouched flake to remove a predefined area from standardized samples of wood. Those using larger flakes were significantly more efficient (i.e., required less time) during this woodworking task. Our results demonstrate that larger flakes could have been preferentially chosen by hominins for woodworking, consistent with previous data generated experimentally in other (non-woodworking) tasks. Moreover, the production of relatively large flakes, such as those at Lomekwi, could have been motivated by woodworking, rather than, or in addition to, butchery. Such issues may also have encouraged the use of Levallois production strategies in later times.